Proteasome inhibitors and Smac mimetics cooperate to induce cell death in diffuse large B‐cell lymphoma by stabilizing NOXA and triggering mitochondrial apoptosis. Issue 5 (8th April 2020) - Dietz, Anna; Dalda, Nahide; Zielke, Svenja; Dittmann, Jessica; van Wijk, Sjoerd J.L.; Vogler, Meike; Fulda, Simone
Abstract : Copy number gains and increased expression levels of cellular Inhibitor of Apoptosis protein (cIAP)1 and cIAP2 have been identified in primary diffuse large B‐cell lymphoma (DLBCL) tissues. Second mitochondria‐derived activator of caspases (Smac) mimetics were designed to antagonize IAP proteins. However, since their effect as single agents is limited, combination treatment represents a strategy for their clinical development. Therefore, we investigated the Smac mimetic BV6 in combination with proteasome inhibitors and analyzed the molecular mechanisms of action. We discovered that BV6 treatment sensitizes DLBCL cells to proteasome inhibition. We show a synergistic decrease in cell viability and induction of apoptosis by BV6/Carfilzomib (CFZ) treatment, which was confirmed by calculation of combination index (CI) and Bliss score. BV6 and CFZ acted together to trigger activation of BAX and BAK, which facilitated cell death, as knockdown of BAX and BAK significantly reduced BV6/CFZ‐mediated cell death. Activation of BAX and BAK was accompanied by loss of mitochondrial membrane potential (MMP) and activation of caspases. Pretreatment with the caspase inhibitor N‐benzyloxycarbonyl‐Val‐Ala‐Asp‐fluoromethylketone (zVAD.fmk) rescued BV6/CFZ‐induced cell death, confirming caspase dependency. Treatment with CFZ alone or in combination with BV6 caused accumulation of NOXA, which was required for cell death, as gene silencing by siRNA or Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9‐mediated NOXA inactivation inhibited BV6/CFZ‐induced cell death. Together, these experiments indicate that BV6 and CFZ cooperatively induce apoptotic cell death via the mitochondrial pathway. These findings emphasize the role of Smac mimetics for sensitizing DLBCL cells to proteasome inhibition with important implications for further (pre)clinical studies. Abstract : What's new? Diffuse large B‐cell lymphoma (DLBCL) is a heterogenous disease, in which existing immunochemotherapy fails in about 40 percent of patients. In particular, poor outcome in DLBCL is correlated with elevated expression of X‐chromosome‐linked inhibitor of apoptosis (XIAP) protein. Here, the Smac mimetic BV6, designed to antagonize XIAP, was found to sensitize DLBCL cells to proteasome inhibition. Combination treatment using BV6 and proteasome inhibitors synergistically induced cell death, which relied on BAX/BAK activation and NOXA accumulation. The findings suggest that combined use of Smac mimetics and proteasome inhibitors is a promising strategy to improve the clinical management of DLBCL.